What is new in robot-assisted radical prostatectomy: a narrative review. Issue 1 (January 2019) - Martini, Alberto; Gandaglia, Giorgio; Briganti, Alberto
Abstract : Purpose of review: The implementation of novel technologies and refinements in the surgical technique are continuously changing the urological surgical scenario. The purpose of this review is to provide surgeons with the latest and most relevant updates in the field of robot-assisted radical prostatectomy (RARP) occurred over the last 12 months. Recent findings: A randomized-controlled trial showed comparable 24-month urinary continence and erectile function recovery between open radical prostatectomy (ORP) and RARP. Recent studies providing Level I evidence on the role of novel approaches such as the Retzius-sparing technique have been published. Nonrandomized studies proposed novel approaches to improve urinary continence and erectile function recovery after surgery without compromising oncologic control that include: preserving the Santorini plexus, a 'collar technique' for apical dissection, a three-layer posterior reconstruction and use of allografts on the neurovascular bundles. Novel surgical platforms have been introduced in an effort to reduce the costs of robotic surgery. Finally, even an experienced open surgeon can benefit from transitioning to RARP Summary: Refinements in the robot-assisted surgical technique and in-patient management might further improve postoperative functional outcomes without compromising oncologic control.